Results of surgical treatment of intertrochanteric and trochanteric fractures in eldery patients - Zhuk, Petro; Kayafa, Andriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Intertrochateric and trochanteric include 52 % out of all femoral fractures. More than 91 % of these fractures occur in people 65 years of age and older. Despite the variety of implants, the number of unsatisfactory treatment outcomes remains high. The fatal outcome due to these fractures is 12–19 % and increases with age. Objective: to evaluate the long-term results of metalloesteosynthesis and hip replacement in an improved method in elderly people with intertrochateric and trochanteric lfemoral fractures. Methods: 156 patients aged 61 to 94 years were examined. Joint replacement was performed in 51 patients (study group), metalloesteosynthesis with PFN, DHS, angular and LCP-plates — 105 (control). The Harris score was used to analyze long-term functional results. Results: satisfactory functional results of the treatment were obtained after the PFN and DHS — (75.13 ± 10.14) and (72.83 ± 17.36) respectively. When using angular and LCP plates, treatment was unsatisfactory — (55.71 ± 19.28) and (67.67 ± 19.73) points, respectively. In the group of total cement endoprosthesis, the results were evaluated as excellent — (93.0 ± 4.33) points; subtotal bipolar — good (86.53 ± 9.7) points; subtotal monopolar — satisfactory (78.23 ± 7.92) points. The total score of excellent and good results in patients in the study group was 76.47 %, the control group — 35.48 %, the poor — 5.88 % and 64.58 % respectively. Conclusion: hip joint replacement in patients over 61 years of age with intertrochateric and trochanteric fractures of the femur gives the best long-term functional results compared to the metalloesteosynthesis.